Characteristics of suicide prevention apps: a content analysis of apps available in Canada and the UK - Lydia Sequeira; Gillian Strudwick; Karen Lascelles; Hwayeon Danielle Shin; Laura Bennett-Poynter; Samantha Groves; Jessica Kemp (BMJ Open)
Objectives We aimed to examine the characteristics, features and content of suicide prevention mobile apps available in app stores in Canada and the UK.Design Suicide prevention apps were identified from Apple and Android app stores between March and April 2023. Apps were screened against predefined inclusion criteria, and duplicate apps were removed. Data were then extracted based on descriptive (eg, genre, app developer), security (eg, password protection) and design features (eg, personalisation options). Content of apps was assessed using the Essential Features Framework. Extracted data were analysed using a content analysis approach including narrative frequencies and descriptive statistics.Data sources Apple and Android app stores between March and April 2023.Eligibility criteria Identified apps were eligible for inclusion if they were: (a) free, (b) developed in the English language, (c) could be downloaded on an Apple or Android device in England or Canada, (d) the focus of the app was suicide prevention and (e) the target users of the app were individuals experiencing suicide-related thoughts and/or behaviours.Data extraction and synthesis Apps were assessed on basic descriptive data (eg, name, genre, developer of the app), alongside security (eg, whether password protection was available) and design features (eg, whether the app could be personalised). App content was examined using the Essential Features Framework.Results 52 suicide prevention apps were included within the review. Most were tailored for the general population and were in English language only. One app had the option to increase app accessibility by offering content presented using sign language. Many apps allowed some form of personalisation by adding text content, however most did not facilitate further customisation such as the ability to upload photo and audio content. All identified apps included content from at least one of the domains of the Essential Features Framework. The most commonly included domains were sources of suicide prevention support, and information about suicide. The domain least frequently included was screening tools followed by wellness content. No identified apps had the ability to be linked to patient medical records.Conclusions The findings of this research present implications for the development of future suicide prevention apps. Development of a co-produced suicide prevention app which is accessible, allows for personalisation and can be integrated into clinical care may present an opportunity to enhance suicide prevention support for individuals experiencing suicidal thoughts and behaviours.